Changes induced by glucose in the plasma membrane properties of pancreatic islets - Cortizo, Ana María (1990)
Partially purified membranes obtained from rat pancreatic isolated islets preincubated for 3 min with 3.3 and 16.6 mM glucose were labelled with 1,6-diphenyl-1,3,5-hexatriene to study fluorescence polarization. Other islets, incubated for 5 min with the same glucose concentration, were extracted and phospholipids separated by thin-layer chromatography. The composition of phospholipids of fatty acids was then studied by gas-liquid chromatography. Arrhenius plots of the microviscosity in membranes obtained from islets exhibited two components, a steeper slope below 18 degrees C and a gentler slope above 18 degrees C, indicating greater flow activation energy at temperatures below the transition point. Exposure of islets to 16.6 mM glucose significantly increased the flow activation energy (delta E), below and above the transition point. Islets incubated for 5 min with 16.6 mM glucose showed an increase in the percentage composition of 12:0 and 18:2 together with a decrease in the 20:2 W6 and 22:3 W3 fatty acids esterified to phospholipids. Regardless of these changes, no significant alterations occurred in the proportion of saturated fatty acids or in the double bond index; these measurements therefore did not account for the effects of glucose concentration in flow activation energy. The thermotropic changes reported here might be the consequence of some degree of disorder induced by glucose upon the membrane structure. This order alteration could either favor the membrane fusion which occurs during the emiocytosis or only reflects the consequence of such a process.